Self-Confidence in Deaf Teenagers at ABC Melati Aisyiyah SLB’S - Purba, Anna Wati Dewi; Nugraha, Arief (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Self-confidence is an essential psychological aspect that affects the development of deaf teenagers. Communication barriers often lead to social challenges, impacting their self-esteem. This study aims to explore the factors influencing self-confidence in deaf adolescents at ABC Melati Aisyiyah Special School (SLB). Using a qualitative phenomenological approach, data were collected through in-depth interviews and observations. The findings indicate that parental support, personal achievements, social interactions, and coping strategies significantly contribute to self-confidence. A positive environment and strong family support play a crucial role in fostering confidence in deaf teenagers.